Unitarity bounds on effective field theories at the LHC - Timothy Cohen; Joel Doss; Xiaochuan Lu (Journal of High Energy Physics, 2022)
Abstract Effective Field Theory (EFT) extensions of the Standard Model are tools to compute observables (e.g. cross sections with partonic center-of-mass energy s ̂ $$ \sqrt{\hat{s}} $$ ) as a systematically improvable expansion suppressed by a new physics scale M. If one is interested in EFT predictions in the parameter space where M < s ̂ $$ \sqrt{\hat{s}} $$ , concerns of self-consistency emerge, which can manifest as a violation of perturbative partial-wave unitarity. However, when we search for the effects of an EFT at a hadron collider with center-of-mass energy s $$ \sqrt{s} $$ using an inclusive strategy, we typically do not have access to the event-by-event value of s ̂ $$ \sqrt{\hat{s}} $$ . This motivates the need for a formalism that incorporates parton distribution functions into the perturbative partial-wave unitarity analysis. Developing such a framework and initiating an exploration of its implications is the goal of this work. Our approach opens up a potentially valid region of the EFT parameter space where M ≪ s $$ \sqrt{s} $$ . We provide evidence that there exist valid EFTs in this parameter space. The perturbative unitarity bounds are sensitive to the details of a given search, an effect we investigate by varying kinematic cuts.